Konsep Budaya Religius dalam Membangun Akhlakul Karimah Peserta Didik di Madrasah Ibtidaiyah - Jannah Ulfah; Suyadi Suyadi (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2021)
The purpose of this study was to describe the concept of religious culture in building the morality of students in Islamic elementary schools. The moral crisis facing Indonesia today makes religious culture very important to be applied in the world of education that demands Islamic elementary school as an effort to build a morality of students. Religious culture in Islamic elementary schools is a way of thinking and how to act based on religious values that underlie the behavior, traditions, and habits that are applied by all Islamic elementary school residents. This research is descriptive qualitative research that started from a literature study by searching various materials related to religious culture and moral. Based on the results of the study, it can be discussed the form of religious culture that can be applied in Islamic schools. Several strategies can be used to build religion in building the morals of students in Islamic schools. Related to this, in implementing religious culture, the active role, and support of various parties involving stakeholders as well. So that, religious culture can runs as expected, to wit can build students' morality. Keywords: Religious Culture, Morality, Islamic Elementary School